STRUCTURE AND DFT CALCULATIONS OF 2-{[3-METHYL-3-PHENYL-CYCLOBUTYL)-THIAZOL-2-YL]-HYDRAZONOMETHYL}-PHENOL - Guntepe, F.; Saracoglu, H.; Caliskan, N.; Yuksektepe, C.; Cukurovali, A. (Pleiades Publishing Ltd, 2011)
The title compound 2-{[3-Methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-hydrazonomethyl}-phenol (C21H21N3S1O1) crystallizes in the P-1 triclinic space group with a = 5.8880(4) angstrom, b = 9.5618(5) angstrom, c = 17.0484(10) angstrom, alpha = 80.214(5)degrees, beta = 80.532(5)degrees, gamma = 80.116(5)degrees. In addition to molecular geometry and packing from X-ray experiment, we have also calculated the molecular geometry and vibrational frequencies of the title compound in the ground state using density functional theory DFT (B3LYP) with the 6-31G(d,p) basis set. Apart from this, the structure of the title compound is characterized by H-1 NMR, C-13 NMR, IR and UV-vis. Spectra, and the experimental emission energies are compared with the HOMO-LUMO energy gaps calculated by the DFT method.
Keywords: crystal structure; IR spectroscopy; DFT calculations